Influence of Training and Technical Assistance of Small Farmers from The Southern Macro-Region of Peru on Agricultural Exports to Brazil by Land - Miguel PANEZ – BENDEZU (Communications of International Proceedings, 2022)
The COVID-19 pandemic has impacted the global agri-food sector. Thus, the need to take measures to make food supply chains work and mitigate the risk of disturbances that can affect the world arises. In this regard, FAO urges countries to support the capacity of small farmers to increase food production (ONU, s.f.). In this context, the study aims to determine how training and technical assistance of small farmers from the southern macro-region of Peru influence agricultural exports to Brazil by land. This research is a mixed method correlational design. The survey and in-depth interview were used as techniques, and a questionnaire and an in-depth interview guide applied to seventeen experts in international trade, agricultural trade and regional development were used as instruments. Results indicate training and technical assistance of small farmers from the southern macro-region of Peru influence agricultural exports to Brazil by land. In conclusion, training and technical assistance of small farmers from the southern macro-region of Peru influence agricultural exports to Brazil by land through technology and local resources for production. More specifically, a higher level of technology utilization and a higher degree of resources provision, allows small farmers to increase their agricultural exports.
Keywords: agricultural exports; training and technical assistance; technology; local resources for production